2018
DOI: 10.1007/s00068-018-0974-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the tranexamic acid in head trauma with no extracranial bleeding: a prospective follow-up of 180 patients

Abstract: TXA is an interesting treatment in haemorrhagic shock. Its efficiency in head trauma is still debated and controversial. Its impact on the mortality and the needs of transfusion or surgery were not demonstrated in this study. Nevertheless, its safety worth to be studied in larger samples as we found a higher rate of pulmonary embolism in the treated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 31 publications
1
58
0
2
Order By: Relevance
“…All studies were published in English. All included studies reported mortality [4,5,[10][11][12][13], three studies reported growth of hemorrhagic mass [10,12,13], four reported disability or dependent [4,5,12,13], three studies reported neurosurgery [11][12][13], three reported vascular embolism [4,5,11], and three reported stroke [4,5,13]. Details of the risk of bias graph ( Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…All studies were published in English. All included studies reported mortality [4,5,[10][11][12][13], three studies reported growth of hemorrhagic mass [10,12,13], four reported disability or dependent [4,5,12,13], three studies reported neurosurgery [11][12][13], three reported vascular embolism [4,5,11], and three reported stroke [4,5,13]. Details of the risk of bias graph ( Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…(Fig. 1) There were a total of 30.522patients from 7 studies [9][10][11][12][13][14][15]. The TXA protocol was mostly 1 g TXA infused over 10 min, followed by IV infusion of 1 g over 8 h. There was 1 study that gave bolus initially and another study that gave initial dose over 30 min.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…TXA was also associated with enhanced clot strength, reduction in trauma-induced coagulopathy, and prevention of hyperfibrinolysis [8]. However, clinical trials demonstrate conflicting results regarding the benefits of the TXA in TBI patients [9][10][11][12]. The risk of thromboembolic complications is also uncertain as one study reported a significantly higher risk of pulmonary embolism (PE) in patients treated with TXA [9].…”
Section: Introductionmentioning
confidence: 99%
“…( Figure 1) There were a total of 30.522 patients from 7 studies. [9][10][11][12][13][14][15] The TXA protocol was mostly 1 g TXA infused over 10 minutes, followed by IV infusion of 1 g over 8 h.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%